Reducing protein through supplementation of limiting amino acids in maize or sorghum based diets for growth and immuno-competence of broiler chickens - Kadam, M M; Mandal, A B; Bhanja, S K; KAUR, Sarabmeet (The Indian Journal of Animal Sciences, 2007)
The objective of this study was to explore possibility of reducing dietary protein through supplementation of limiting amino acids (methionine, lysine and threonine) in diets of broiler chickens following ideal protein concept. Day-old broiler chicks (128) were selected randomly, weighed and distributed into 16 groups of 8 chicks each. They were offered 4 dietary treatments in quadruplicated groups. The dietary treatments were formulated basing on maize and sorghum as a major source of cereal with high protein (21.6-20.0%)and reduced protein (19.8-18.3%) during starting and finishing period, respectively, at each cereal in 2 x 2 completely randomized designs. The protein concentration in high protein diet was increased to meet the requirement of L-threonine, the most costly limiting amino acid and low protein diet was supplemented with synthetic L-threonine at each cereal. Obviously the synthetic lysine and methionine were supplemented in both (high and low protein) diets to meet their requirement as suggested by NRC (1994). The body weight gain did not differ significantly due to protein level and interaction of protein and grain type. The body weight gain was higher during 0-28 d of age in maize based diets, while during 28-49 and 0-49 d of age in sorghum based diets. The feed intake and feed conversion ratio (FCR) did not differ due to interaction or protein levels. Higher feed intake was recorded in sorghum diets compared to maize during 28-49 d of age. Better FCR was calculated for 28-49 d of age on sorghum diet compared to maize-based diet while FCR did not differ during 0-28 or 0-49 d of age. Efficient utilization of protein and energy was seen in maize based diets during 0-28 d and in sorghum diets during 28- 49 d of age. The cellular and humoral immune responses, relative weight of different immune organs and feed cost (per kg gain) did not differ due to protein levels, grain type or their interaction. However, birds fed on sorghum had significantly higher feed cost per kg gain than maize based diet during 0-28 d of age. The results indicated that the protein concentration in broiler diet could be reduced (1.7 to 1.8% in starter and finisher diets) through supplementation of limiting amino acids without affecting growth performance, immuno-responsiveness and feed-cost of production during summer. White sorghum was found to be superior to maize during finisher stage of broiler production.